Project work: restructuration and implementation of an onboarding program - Santos, Francisco Maria Lamego de Albuquerque Vilas (2020)
Over the last few years, human resources systems that link human resources practices, people's attitudes and organizations' performances, are growing in terms of importance and, consequently, investment in organizations. In this sense, it became interesting to study how these human resources systems or practices influence the whole employee experience, which starts on day one of any new hire. In order to ensure a proper integration and induction of a newcomer, onboarding programs - the specific practices initiated by an organization or its agents to facilitate employee adjustment to new roles - are gaining each day more relevance in organizations and Human Resources teams are now changing the paradigm of seeing induction programs as an investment rather than a cost. In the light of this, a pilot onboarding program was designed and executed for a company operating in the insurance sector. Moreover, this pilot program was tested on twenty newcomers and evaluated through an online survey, in order to assess their satisfaction and opinion. The results showed a great increase in terms of satisfaction, when comparing to the previous onboarding program, especially when we talk about onboarding and job satisfaction, understanding the company and the new role in it. Furthermore, the employee experience was also improved for these newcomers.